“É sinal que a chuva chegou no sertão”: imagem, memória e representação na narrativa cinematográfica sob o ditame de Rude Almajesto: sinais de chuva - Silva, Mateus Soares (2024)
This dissertation analyzes the documentary Sob o ditame de Rude Almajesto: sinais de chuva (1976), written by filmmaker Olney São Paulo, which covers conceptions of the Sertão based on a discourse of rustic semiotics that can only be accessed by thinking about the Sertão. This documentary is a cinematographic production disconnected from Hollywood grammar and the standards of "official" cinematography, also investigating the impact of the Cinema Novo movement in the Brazilian context, highlighting how this movement does not encompass all cinematographic productions of the time. Through the analysis of this work by filmmaker Olney São Paulo, who acted as a cultural mediator between the traditional and the modern, the study explores and problematizes sertanejo knowledge, defending their ways of life and sociocultural traits. The focus lies on the representation of cultural practices related to rain forecasting, offering a unique perspective on the empirical science of the farmer and highlighting the originality of this knowledge in sertaneja culture. The critical analysis of this documentary contributes to a deeper understanding of the sociocultural issues addressed modern cinema.